Study of Ga-Polar and N-Polar GaN-Based Green VCSELs by Simulation - Ya-Chao Wang; Yan-Hui Chen; Zhong-Ming Zheng; Tao Yang; Yang Mei; Lei-Ying Ying; Bao-Ping Zhang (IEEE Photonics Journal, 2024)
Gallium Nitride (GaN)-based vertical-cavity surface-emitting lasers (VCSELs) in green spectral region face the difficulty of the “green gap”. One of the main obstacles is the strong polarization electric field in GaN-based materials, which leads to a strong quantum confinement Stark effect (QCSE) and reduces the efficiency of radiative recombination. In this study, we systemically simulated and compared the optical and electrical performance of GaN-based green VCSELs based on Ga-polar and N-polar InGaN quantum wells (QWs) by using the software of PICS3D. The results show that the light-output power of N-polar VCSEL is greatly improved by 183% compared to Ga-polar VCSEL at an injection current of 20 mA, while the threshold current is reduced by 49%. The improved performance is mainly attributed to: 1) the decreased QCSE; 2) the more efficient carrier injection, and 3) the reduced carrier leakage in N-polar devices. The results of this study suggest that N-polar based GaN is promising for the realization of high-performance green VCSELs, which can provide a guidance for the fabrication of high-power green VCSELs.